2000
DOI: 10.1046/j.1365-2834.2000.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a model to manage change: reflection on a critical incident in a focus group setting. An innovative approach

Abstract: Aim  This paper describes the development of a model to manage and evaluate the management of change. The Change Management Model may provide nurse managers or change agents with a structured and measurable model for managing and evaluating the change process. A measurement constructs tools to further assist the evaluation process is also described. Background  The author argues that certain key variables can be identified which contribute to the successful implementation of change. These variables include cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Many authors have shown that providing information can help reduce uncertainty and anxiety (Johnson et al. 1996), and this condition is essential for creating openness toward change initiatives (Carney 2000, Wanberg & Banas 2000, Stanley et al. 2005).…”
Section: Change‐related Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have shown that providing information can help reduce uncertainty and anxiety (Johnson et al. 1996), and this condition is essential for creating openness toward change initiatives (Carney 2000, Wanberg & Banas 2000, Stanley et al. 2005).…”
Section: Change‐related Communicationmentioning
confidence: 99%
“…Managing the process of change has become a fundamental skill for all nurse managers (Carney 2000). Quinn (2004) argued that poor quality of leadership during the process of change was strongly linked to failure of change efforts.…”
Section: Leader-member Exchange (Lmx)mentioning
confidence: 99%
“…This would guide the planning and implementation of the tools and could also facilitate inclusion of the nurses' feeling in the choice of tools, rather than feeling that they were being imposed on them. Change theory suggests that change is much more likely to succeed if the key players are involved in the planning stages (Carney, 2000;Lewin, 1951). It has been suggested that the change agent -that is, the person who is facilitating the change -needs to identify and analyse the driving force for change and to analyse and, if possible, manage it (Kanter, 1995).…”
Section: Aimsmentioning
confidence: 99%
“…2008), these strategies might support specialist nurses to update and expand their roles in relation to environmental changes. Problem identification, assertiveness, negotiation and discussion skills and system thinking were cited as necessary for CNSs/CNs to develop, and are similar to skills for managing change in an organization (Carney 2000). Our findings suggest that nurse administrators could contribute to effective implementation of specialist nurses’ roles not only by clarifying their roles but also by empowering them to keep up with changing organizational needs.…”
Section: Discussionmentioning
confidence: 99%